Planificación y Desarrollo Turístico en el Cantón Chimbo, Provincia Bolívar - Ulloa Toalombo, Diego Germán (2019)
This research project was carried out looking for the tourist development of Chimbo canton, which suffers from inadequate planning in terms of tourism. For this reason, this research is carried out to solve the mentioned problem. The progress will be raised under strict levels of social responsibility and commitment. For these reasons, the population, tourism workers, and the Tourism Department unit will work according to the objectives set to thereby boost tourism to canton Chimbo. This research has several backgrounds of authors who contribute to the research with guidance information for the development. In the end, a proposal is stated which demonstrates strategies; functions and processes to follow that will be very helpful for the tourist development of the canton. The need to improve the attention and service to tourists, in order to ensure their survival in the tourism market, for which it is convenient to implement a plan for the correct tourism development, which through techniques and procedures will help the promotion and its tourist positioning of the Chimbo canton.